Politics and economics of second-best regulation of greenhouse gases: the importance of regulatory credibility - Valentina Bosetti; David G. Victor (Fondazione Eni Enrico Mattei (FEEM), 2010)
Modellers have examined a wide array of ideal-world scenarios for regulation of greenhouse gases. In this ideal world, all countries limit emissions from all economic sectors; regulations are implemented by intelligent, well-informed forward-looking agents; all abatement options, such as new energy technologies and forestry offsets, are available; trade in goods, services and emission credits is free and unfettered. Here we systematically explore more plausible second-best worlds. While analysts have given inordinate attention to which countries participate in regulation-what we call 'variable geometry'-which has a strikingly small impact on total world cost of carbon regulations if international trade in emission credits allows economies to equilibrate. Limits on emission trading raise those costs, but by a much smaller amount than expected because even modest amounts of emission trading (less than 15% of abatement in a plausible scenario that varies the geometry of effort) have a large cost-reducing impact. Second best scenarios that see one sector regulated more aggressively and rapidly than others do not impose much extra burden when compared with optimal all-sector scenarios provided that regulations begin in the power sector. Indeed, some forms of trade regulation might decrease the financial flows associated to a carbon policy thus increasing political feasibility of the climate agreement. Much more important than variable geometry, trading and sectors is another factor that analysts have largely ignored: credibility. In the real world governments find it difficult to craft and implement credible international regulations and thus agents are unable to be so forward-looking as assumed in ideal-world modelling exercises. As credibility declines the cost of coordinated international regulation skyrockets-even in developing countries that are likely to delay their adoption of binding limits on emissions. Because international institutions such as treaties are usually weak, governments must rely on their own actions to boost regulatory credibility-for example, governments might 'pre-commit' international regulations into domestic law before international negotiations are finally settled, thus boosting credibility. In our scenarios, China alone would be a net beneficiary of pre-commitment that advances its carbon limits two decades (from 2030, in our scenario, to today) if doing so would make international regulations more credible and thus encourage Chinese firms to invest with a clearer eye to the future. Overall, low credibility is up to 6 times more important in driving higher world costs for carbon regulations when compared with variable geometry, limits on emission trading and variable sectors. In this paper, we have not explored the other major dimension to the second-best: the lack of timely availability of the full range of abatement options, although our results suggest that even this will be less consequential than credibility.
Keywords: Q5; Q58; 330; Greenhouse Gases; Second-best Regulation; Luftverunreinigung; Kohlendioxid; Umweltpolitik; Internationale Umweltpolitik; Second Best